Trimetazidine Reduces Cardiac Fibrosis in Rats by Inhibiting NOX2-Mediated Endothelial-to-Mesenchymal Transition - Chen X; Xia X; Dong T; Lin Z; Du L; Zhou H (Dove Medical Press, 2022)
Xingxing Chen,* Xue Xia,* Tiancheng Dong, Zhiwei Lin, Leilei Du, Hao Zhou Department of Cardiology, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Hao Zhou, Department of Cardiology, the First Affiliated Hospital of Wenzhou Medical University, NanBai Xiang Avenue, Ouhai District, Wenzhou, 325000, People's Republic of China, Tel +86 1 396 880 1939, Fax +86 577 555 79796, Email wyzh66@126.comPurpose: Endothelial-to-mesenchymal transition (EndMT) is an important mechanism underlying cardiac fibrosis. The anti-ischemic drug trimetazidine (TMZ) is reportedly useful in ventricular remodeling and associated with NADPH oxidase (NOX) 2. This study aimed to investigate the possible effect of TMZ on cardiac fibrosis exerted via the inhibition of NOX2-mediated EndMT.Methods: A cardiac fibrosis model was established in Sprague-Dawley rats through a subcutaneous injection of isoproterenol (ISO, 5 mg/kg/d). Echocardiographic parameters, myocardial fibrosis, NOX2 expression and EndMT were assessed. An in vitro model of EndMT was developed using human umbilical vein endothelial cells (HUVECs) via treatment with transforming growth factor-β (TGF-β) at 10 ng/mL for 24 h. HUVECs were administrated with TMZ or TMZ and lentivirus, the expression of EndMT and related proteins was observed by wound healing assay, immunoblotting, and immunofluorescence.Results: Rats injected with ISO exhibited severe interstitial cardiac fibrosis and perivascular fibrosis, decreased left ventricular ejection fraction, and increased NOX activity. TMZ treatment mitigated cardiac fibrosis, ameliorated left ventricular dysfunction, and reduced NOX activity. In addition, TMZ effectively inhibited EndMT in ISO-treated rat hearts and TGF-β-treated HUVECs, as manifested by increased CD31 expression, decreased α-SMA expression, and suppressed cell migration. Compared with the control group, the expression of NOX2, nuclear factor-κB (NF-κB), and Snail was increased in vivo and in vitro but decreased with TMZ treatment. Furthermore, the overexpression of NOX2 by lentivirus abolished the protective effects of TMZ on TGF-β-induced EndMT.Conclusion: TMZ may ameliorate EndMT and ISO-induced cardiac fibrosis through the NOX2/NF-κB/Snail pathway. The findings of the study may provide new insights into the potential role of TMZ in the pathophysiology of cardiac fibrosis.Keywords: trimetazidine, endothelial-to-mesenchymal transition, cardiac fibrosis, NADPH oxidase 2